PRINT-ON-DEMAND FASHION MODELS FOR REDUCING OVERPRODUCTION AND ENVIRONMENTAL WASTE IN THE FASHION INDUSTRY - Mizanur Rahman (International Journal of Innovative Technologies in Social Science, 2024)
The fashion industry significantly contributes to environmental waste and overproduction which result in substantial fabric waste and excess inventories. Print-on-Demand (POD) fashion models have appeared as a solution to these challenges by manufacturing items when receiving of an order. This strategy follow sustainability principles by utilizing digital printing technology to enhance production efficiency, minimize resource consumption and increase consumer preference for customization. This study evaluates the efficacy of POD models based on academic literature in mitigating overproduction and environmental waste in the fashion industry.The results of this study highlights that POD minimizes waste and underscores that POD models are an essential step in transforming the fashion industry into a more sustainable and ethical company, capable of balancing responsibility for the environment with economic feasibility.